Personal and Social Education Carried out by Polish Primary Schools during the COVID-19 Pandemic – Two Insights into Early Childhood Education - Zubala, Ewelina; Wichrowska, Kamila; Marchlik, Paulina (Przegląd Badań Edukacyjnych (Educational Studies Review), 2022)
Remote education caused by the spread of SARS-CoV-2 virus proved to be a difficult experience for all of its participants. Teachers and parents faced logistical and organisational challenges in teaching young children, but were equally affected by educational and socio-emotional development issues. The aim of this article is to present how personal and social education (PSE) was carried out by Polish teachers of the first three grades of primary school during remote classes. The authors conducted an empirical qualitative study in early 2021, before the third school closures in Poland. The study involved 20 teachers and 20 parents of pupils in grades 1–3 of public primary schools from the Mazovian voivodeship. A semi-structured interview was used to explore the experiences of the respondents and obtain information to address the research question: “How was personal and social education carried out by teachers during remote education in grades 1–3 of Polish primary schools in the COVID-19 pandemic?”, which referred to the activities used by teachers to implement remote personal and social education, as well as the parents’ and teachers’ opinions as regards this process. The conclusion pointed out by the majority of respondents was the need to adapt to utterly new conditions, to focus on the emotional and social needs of the youngest pupils being the result of an unfamiliar, remote reality. The PSE with the youngest pupils during the pandemic was carried out in two ways: prevention and intervention. Prevention took place during everyday meetings, and took the form of a talk about their experiences from the previous day or anything that mattered to children within the time of the online classes. Intervention took place only when needed, and took such forms as an individual conversation with the pupil, a conversation with a parent or other.